99mTc‐labeled NGR‐chlorambucil conjugate, 99mTc‐HYNIC‐CLB‐c(NGR) for targeted chemotherapy and molecular imaging. (21st June 2017) - Vats, Kusum; Satpati, Drishty; Sharma, Rohit; Kumar, Chandan; Sarma, Haladhar D.; Dash, Ashutosh
Abstract : Targeted delivery of chemotherapeutic drug at the tumor site enhances the efficacy with minimum systemic exposure. Towards this, drugs conjugated with peptides having affinity towards a particular molecular target are recognized as affective agents for targeted chemotherapy. Thus, in the present study, tumor‐homing asparagine‐glycine‐arginine (NGR) peptide ligand was conjugated to DNA alkylating nitrogen mustard, chlorambucil (CLB). The peptide‐drug conjugate (PDC), CLB‐c(NGR), was radiolabeled with 99m Tc‐HYNIC core to trace its pharmacokinetics and biodistribution pattern. In vitro cell‐binding studies of 99m Tc‐HYNIC‐CLB‐c(NGR) were conducted in murine melanoma B16F10 cells. The cytotoxicity studies conducted by incubation of the peptide/drug/PDC with B16F10 cells demonstrated enhanced cytotoxic effect of PDC in comparison to either the peptide or the drug alone. In vivo biodistribution studies in C57BL6 mice bearing melanoma tumor showed maximum tumor uptake at 30 minutes pi (2.45 ± 0.28% ID/g), which reduced to 0.77 ± 0.1% ID /g at 3 hours pi. The radiotracer being hydrophilic cleared rapidly from the heart, lungs, liver, and muscle. The tumor‐to‐blood and tumor‐to‐muscle ratios improved with time. This study opens avenues for conjugation of other targeting peptides with the drug CLB for enhanced toxicity at the diseased site. Abstract : In this study, the drug chlorambucil (CLB) was conjugated with the peptide c(NGR) to prepare the peptide‐drug conjugate (PDC), CLB‐c(asparagine‐glycine‐arginine [NGR]), for targeted chemotherapy. The PDC exhibited enhanced cell cytotoxicity than peptide, cNGR or drug, CLB alone. The radiolabeled PDC, 99m Tc‐HYNIC‐CLB‐c(NGR), being highly hydrophilic cleared rapidly from the nontarget organs during biodistribution studies. The PDCs thus have a promising potential for future use in targeted chemotherapy.